The jungle book - Kipling,Rudyard (Puffin books, London, 2024)
The Jungle Book by Rudyard Kipling is a classic collection of stories, first published in 1894. It primarily follows the adventures of Mowgli, a young boy raised by wolves in the Indian jungle, and explores themes of nature, identity, and survival.